Intervenciones de enfermería en la prevención del dengue en zonas endémica: revisión integrativa: Nursing care for dengue prevention in endemic areas - Hilario Povis, Rossana Ines (2025)
An integrative review was conducted to evaluate nursing interventions in dengue prevention in endemic areas. The literature search was carried out using the SciELO, Science Direct, PubMed, and Scopus databases. The methodological evaluation followed the model proposed by Whittemore and Knafl (2005), which allows for the integration of qualitative and quantitative findings in integrative reviews. The results show that nursing-led health education, based on Swanson’s theory of care and Nola Pender’s health promotion model, is an effective strategy for improving knowledge, strengthening self-efficacy, and developing preventive skills against dengue in vulnerable populations. Educational interventions transcend the transmission of information, as they promote sustainable behavioral changes, increasing intrinsic motivation, reducing barriers, and reinforcing the perception of benefits around prevention. International studies conducted in Indonesia, Thailand, Peru, Colombia, and India agree that integrated management, community participation, and family and student empowerment are essential pillars of vector control. In this context, both the family and educational settings are consolidated as strategic centers of social empowerment, contributing to the sustainability of preventive practices. Likewise, the importance of promoting an intersectoral and culturally contextualized approach that coordinates the efforts of health systems, educational institutions, local governments, and communities is highlighted. It is concluded that the spread of arboviruses and the presence of severe forms of dengue reinforce the need to consolidate the essential role of nursing in primary prevention through sustainable community interventions based on scientific evidence.